Effects of microbe-derived antioxidants on growth performance, hepatic oxidative stress, mitochondrial function and cell apoptosis in weaning piglets - Chengbing Yu; Yuxiao Luo; Cheng Shen; Zhen Luo; Hongcai Zhang; Jing Zhang; Weina Xu; Jianxiong Xu (Journal of Animal Science and Biotechnology)
Abstract Background Weaning causes redox dyshomeostasis in piglets, which leads to hepatic oxidative damage. Microbe-derived antioxidants (MA) have great potential for anti-oxidation. This study aimed to investigate changes in hepatic redox system, mitochondrial function and apoptosis after weaning, and effects of MA on growth performance and liver health in weaning piglets. Methods This study consisted of 2 experiments. In the both experiments, piglets were weaned at 21 days of age. In Exp. 1, at 21 (W0), 22 (W1), 25 (W4), 28 (W7), and 35 (W14) days of age, 6 piglets were slaughtered at each timepoint. In Exp. 2, piglets were divided into 2 groups: one received MA gavage (MA) and the other received saline gavage (CON). At 25 days of age, 6 piglets from each group were sacrificed. Results In Exp. 1, weaning caused growth inhibition and liver developmental retardation from W0 to W4. The mRNA sequencing between W0 and W4 revealed that pathways related to “regulation of apoptotic process” and “reactive oxygen species metabolic process” were enriched. Further study showed that weaning led to higher hepatic content of reactive oxygen species (ROS), H2O2 and O2 −. Weaning enhanced mitochondrial fission and suppressed their fusion, activated mitophagy, thus triggering cell apoptosis. In Exp. 2, MA improved growth performance of piglets with higher average daily gain (ADG) and average daily feed intake (ADFI). The hepatic ROS, as well as products of oxidative damage malonaldehyde (MDA) and 8-hydroxy-2′-deoxyguanosine (8-OHdG) in the MA group decreased significantly than that of the CON group. The MA elevated mitochondrial membrane potential, increased activity of mitochondrial respiratory chain complexes (MRC) I and IV, enhanced mitochondrial fusion and reduced mitophagy, thus decreasing cell apoptosis. Conclusions The present study showed that MA improved the growth performance of weaning piglets and reversed weaning-induced oxidative damage, mitochondrial dysfunction, and apoptosis. Our results suggested that MA had promising prospects for maintaining liver health in weaning piglets and provided a reference for studies of liver diseases in humans. Graphical Abstract